Tunable multiple non-volatile resistance states in multiferroic tunnel junctions based on sliding ferroelectric PtTe2 - Liu, Yulin; Zhou, Yan-Hong; Zheng, Xiaohong; Xie, Fang; Liu, Zhimin (New journal of physics, 2025)
Multiferroic tunnel junctions (MFTJs) own significant potential application in non-volatile memory devices due to their multifunctional characteristics, which has attracted widespread attention. The recent advancements in van der Waals (vdW) multiferroic materials have successfully combined ferromagnetism and ferroelectricity, providing an ideal platform for studying MFTJs at the atomic scale. In this study, we theoretically investigate the spin-dependent transport properties of vdW MFTJs based on sliding ferroelectric barrier layers of PtTe2 using first principles based on density functional theory. Our research shows that multiple non-volatile resistance states can be achieved by controlling the polarization direction of the ferroelectric barrier in Fe3GaTe2/PtTe2/Fe3GeTe2 vdW MFTJs and the magnetization direction of the ferromagnetic electrodes. Specifically, as the ferroelectric material undergoes slippage, the polarization of the ferroelectric barrier shifts from left-oriented (P←) to right-oriented (P→), which induces the tunneling magnetoresistance ratio at the Fermi level increasing from 2.7×107% to 5.7×107%. As the magnetization direction of the ferromagnetic electrodes changes from parallel (M↑↑) to antiparallel (M↑↓), the tunneling electroresistance ratio significantly rises from 9.52% to 155%. Moreover, a nearly 100% spin-filtering efficiency is observed in the four states of MFTJs and the resistance area (RA) product is very small, with the minimum RA product at the Fermi level 0.033 Ω⋅μm2. This research highlights the potential use of the sliding ferroelectricity in bilayer PtTe2 in constructing multistate non-volatile memory and spin filter, and can be used for the development of multifunctional electronic devices.